2013
DOI: 10.1111/ajd.12010
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis uncovered – measuring burden of disease impact in a survey of Australians with psoriasis

Abstract: Psoriasis imposes a significant psychosocial burden on the lives of patients, including a profound impact upon their personal and professional relationships, social interactions and quality of life, to a degree comparable to other serious chronic conditions. This study highlights the importance of collaboration between primary and specialist health-care providers in developing patient management strategies that address the spectrum of physical and psychological manifestations associated with psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…[P9: prescribed topical therapy but using herbal therapies] reducing or ending participation in physical activities. These factors are recognized problems in this population [43][44][45] and all were perceived as contributing to ongoing psychological distress. The need to manage psoriasis symptoms with prescribed medication conflicted with the need to manage concerns about adverse effects.…”
Section: Discussionmentioning
confidence: 95%
“…[P9: prescribed topical therapy but using herbal therapies] reducing or ending participation in physical activities. These factors are recognized problems in this population [43][44][45] and all were perceived as contributing to ongoing psychological distress. The need to manage psoriasis symptoms with prescribed medication conflicted with the need to manage concerns about adverse effects.…”
Section: Discussionmentioning
confidence: 95%
“…[20][21][22][23][24][25] The study reported here took an innovative approach of evaluating broad aspects of patient experience, encompassing questions on symptom severity, treatment efficacy, and the impact of psoriasis on aspects of healthrelated QoL, such as sleep, work productivity and relationships. [20][21][22][23][24][25] The study reported here took an innovative approach of evaluating broad aspects of patient experience, encompassing questions on symptom severity, treatment efficacy, and the impact of psoriasis on aspects of healthrelated QoL, such as sleep, work productivity and relationships.…”
Section: Discussionmentioning
confidence: 99%
“…While patient perceptions of and attitudes about psoriasis and its treatment are considered increasingly paramount in managing the disease, few studies have systematically elicited patients' perspectives on a large scale. [20][21][22][23][24][25] The study reported here took an innovative approach of evaluating broad aspects of patient experience, encompassing questions on symptom severity, treatment efficacy, and the impact of psoriasis on aspects of healthrelated QoL, such as sleep, work productivity and relationships. The survey extended globally, recruiting 8338 participants from 31 countries.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is associated with high levels of physical and psychological disability, 2-5 comorbidities 6-10 and significant life impact. 11,12 While individuals with psoriasis have additional risk factors for 13 and higher mortality from 14 cardiovascular disease, recent evidence suggests that psoriasis in the absence of inflammatory arthritis is not an independent risk factor. 13 Unhealthy lifestyle behaviours [15][16][17][18][19][20] and obesity 21 are more common in individuals with psoriasis, complicating understanding of comorbidities 13,18 and contributing to risks of psoriasis onset and/or exacerbation, 16,[22][23][24][25][26][27] although patients and nonspecialist clinicians may be unaware of these associations.…”
Section: What's Already Known About This Topic?mentioning
confidence: 99%
“…Psoriasis is a complex, long‐term inflammatory skin condition affecting at least 2% of the U.K. population . It is associated with high levels of physical and psychological disability, comorbidities and significant life impact . While individuals with psoriasis have additional risk factors for and higher mortality from cardiovascular disease, recent evidence suggests that psoriasis in the absence of inflammatory arthritis is not an independent risk factor …”
mentioning
confidence: 99%